Can we improve the definition of high‐risk, hormone naïve, non‐metastatic prostate cancer?. (February 2014) - Tombal, Bertrand; Alcaraz, Antonio; James, Nicholas; Valdagni, Riccardo; Irani, Jacques
Abstract : To identify criteria beyond Tumour‐Node‐Metastasis (TMN)‐, prostate‐specific antigen (PSA)‐ and Gleason score‐based standard classifications to enhance the stratification of non‐metastatic high‐risk prostate cancer. A detailed search of the literature was performed using PubMed. The authors reviewed the literature and used a modified Delphi approach to identify relevant approaches to enhance standard classifications. Specific criteria for high‐risk prostate cancer vary across guidelines and clinical trials, reflecting the differing perspectives concerning the definition of 'risk' between different specialities within the urology/radiation oncology community. In addition to the present classifications, evidence exists that the measure of cancer volume can provide additional prognostic value. More accurate imaging, especially multiparametric magnetic resonance imaging can also provide information concerning staging and cancer volume, and thus may assist in the identification of patients with high‐risk prostate cancer. A refined definition of non‐metastatic high‐risk prostate cancer is proposed. Within this high‐risk cohort, patients with multiple high‐risk criteria are especially at risk of prostate cancer‐specific mortality.